Development and validation of academic involution scale for college students - He, Yiqing; Liu, Xinyi (Scientific reports, 2025)
To develop a scale for assessing the involution among Chinese college students, and to test its reliability and validity within the context of higher education. The scale was developed based on in-depth interviews and existing competition scales. dataset 1 (n = 220) was utilized for exploratory factor analysis, and dataset 2 (n = 500) was employed for confirmatory factor analysis (CFA), convergent validity and discriminant validity test, reliability test, criterion validity test, and difference analysis on demographics. The final scale comprises 26 items across six factors: excessive comparison (EC), futile effort (FE), hyper-competition (HC), negative moods (NM), academic opportunism (AO), and vicious competition (VC). The six factor model showed satisfactory model fit in CFA: χ 2 /df = 2.493, NFI = 0.940, CFI = 0.963, RMSEA = 0.055. Standardized factor loadings ranged from 0.593 to 0.902. Composite reliability (CR) values were greater than 0.7.and average variance extracted (AVE) values were predominantly higher than 0.45. Discriminant validity test found that six factor model showed the best model fit than less factors. Criterion validity test indicated that the six factors of academic involution were significantly correlated with academic anxiety. The reliability of each factor ranged from 0.763 to 0.838, split-half reliability was 0.760, demonstrating satisfactory reliability. There were significant differences in academic involution in terms of institutional tier and grade point average (GPA) ranking. This study initially identified the main characteristics of academic involution among college students. The developed scale has good reliability and validity and can be used as a measurement tool.